From genotype to protein: how the 308 G/A polymorphism of the TNF-α gene is associated with TNF-α protein levels in patients with Hashimoto’s thyroiditis - R. R. Rahimova; G. Azizova; A. E. Rahimzade; M. Mehdiyev; G. S. Dashdamirova; S. A. Bagirova (Zaporožskij Medicinskij Žurnal)
Aim. To study the 308 G/A polymorphism of the TNF-a gene and its influence on serum levels of TNF-a protein in patients with Hashimoto’s thyroiditis (HT) among the Azerbaijan population.